Bioenergy production from cotton straws using different pretreatment methods - Yoruklu, Hulya Civelek; Koroglu, Emre Oguz; Ozdemir, Oguz Kaan; Demir, Ahmet; Ozkaya, Bestami (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Cotton straws are one of the most produced agricultural wastes in Turkey and getting attention by not being consumed as animal feed or an industrial stock and having a huge potential in clean energy production. In this study, different pretreatment methods for the conversion of cotton straw to sugar then biohydrogen and biomethane production from cotton straw were examined. The energy potential of cotton straw in case of an evaluation of these biomass residues was also determined using fuel cell technology. Acid pretreatment provided the highest yield in biogas formation as well as sugar extraction from the raw sample. The highest biohydrogen and biomethane production were obtained as 33 mL H-2/g VS and 83 mL CH4/g VS, respectively. Concomitantly, the maximum power peaks in PEM fuel cell studies were observed as 0.45 W/cm(2) and 0.23 W/cm(2) with current densities of 1.086 A/cm(2) and 0.522 A/cm(2) when the fuel cell was fed with pure H-2 and biogas, respectively. This suggested that acid pretreatment is more suitable for cotton straw management in sustainable and renewable ways and the results demonstrated that PEM fuel cell is a promising clean technology for energy generation from cotton straw. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Cotton straw; Pretreatment; Biohydrogen; Biomethane; PEM fuel cell; FERMENTATIVE HYDROGEN-PRODUCTION; ACTIVE SURFACE-AREA; BIOMETHANE PRODUCTION; ANAEROBIC-DIGESTION; BIOGAS PRODUCTION; BIOHYDROGEN PRODUCTION; METHANE PRODUCTION; HYDROLYSIS; ENHANCEMENT; PLATINUM; Chemistry; Electrochemistry; Energy & Fuels